A bibliometric study on architectural education and participation (2000-2024) - Aydin, Hanim Gul; Birer, Emel (TAYLOR & FRANCIS LTD, 2026)
This research presents a systematic literature analysis based on bibliometric data regarding the evolving key concepts of participation in the context of architectural education and environmental crises. The aim of the research is to identify potential research opportunities in the area of participatory architectural education. The Web of Science (WOS) database was opted for the bibliometric analysis process due to its access to multidisciplinary sources and compatible file formats as the analysis software. In this context, articles published between 2000 and 2024 were screened, and a comprehensive filtering was conducted in accordance with the established inclusion and exclusion criteria. As a result, a total of 256 articles were selected. The selected articles were recorded based on bibliographic data such as publication year, language, journal, title, author, institution, keywords, document type, abstract, and citation count. Vosviewer (version 1.6.20) software was used for the bibliometric analysis. The findings show that more research and documents are needed from different countries, sources and authors on participatory architectural education. This research provides a reference for future studies by revealing current concepts, prominent keywords, important authors, documents, sources, institutions, and references on participatory architectural education.
Keywords: Bibliometric analysis; participatory architectural education; interdisciplinary and collaborative learning; co-design; DESIGN; Art